(3CeGdj GdbGdjs - (3CHh Ydj GdbGdj , ESeGYjd Hf GdbGSe Hf YHOhf Hf gGQhf Hf YjSi Hf eMeO Hf SdeGf, CHh Ydj,J (B356 (3g` s ((3CMeO Hf eMeO Hf YHOGdbGOQ GdcdGdj s)
(3ChdgG (B:s
(3CeG HYO(B: (3aEffj deG QCjJ GdYde CfaS HVGYI, hCjbfJ Cf WdHg CaVd JLGQI, aGZJQHJ ddQhGjI hdReJ GdYdeGA ddOQGjI aCeddJ gPG GdcJGH ef MaXj, hChOYJg s
(3BNQgG (B:s
(3jbhd(B: (3cfJ SjakG cdjdkG dG jDKQ EdG cCKQ GdLYGQ hGdOQGf hGdcgGe hGdcgje(B: (3Gdcdjd gfG Je GdfUa GdChd ef GdCeGdj s
(3GdfSNI HgG MhGTs
(3Ydi ghGeTgG TQhM hJYdjbGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQM hGedGA s
Keywords: (3GdCOHs